LEGAL PROTECTION OF OUTSOURCING WORKERS AGAINST EMPLOYERS' ARBITRARY ACTIONS IN TERMINATION OF EMPLOYMENT RELATIONSHIPS IN INDONESIA BASED ON THE JOB CREATION LAW - Lestari, Rr. Winarti Pudji; Santoso, Imam Budi; Setiady, Tri (Jurnal Ilmiah Advokasi, 2025)
Currently business competition is getting tighter, many companies are choosing to implement an outsourcing system because this system is felt to be more effective. In the outsourcing system, it is easier for employers to terminate employment relationships (PHK), so this outsourcing system cannot provide job security for workers. In fact, guarantees to work and earn a decent living are the constitutional rights of every citizen. The state has regulated the protection of workers' rights and guaranteed continuity of work in the Job Creation Law through the TUPE concept. However, these regulations have not been equipped with clearer regulations so they are still difficult to implement. The aim of this research is to examine and understand the legal protection for outsourcing workers from arbitrariness by employers in the implementation of layoffs and to examine and analyze the principles of outsourcing so that there is no arbitrariness by employers in the implementation of layoffs. This research uses a normative juridical approach, namely an approach carried out on the basis of the main legal material by examining theories, concepts, legal principles and statutory regulations related to this research. The author also uses a comparative legal approach method, namely comparing law in different countries as a system (law is seen as a system), so that based on the differences, researchers are able to provide conclusions regarding a legal issue. The outsourcing system in Indonesia currently does not reflect justice for outsourcers. There needs to be legal reform so that worker protection can be improved without leaving the flexibility of the outsourcing system behind. From this research, the author was able to find a prospective concept for developing better outsourcing regulations. Keywords:  Legal Protection; Outsourcing; Arbitrariness; Termination of Employment.